MicroRNA Regulatory Mechanisms on Citrus sinensis leaves to Magnesium-Deficiency - Ma, Cui-Lan; Qi, Yi-Ping; Liang, Wei-Wei; Yang, Lin-Tong; Lu, Yi-Bin; Guo, Peng; Ye, Xin; Chen, Li-Song (Frontiers in Plant Science, 2016)
Magnesium (Mg)-deficiency, which affects crop productivity and quality, widespreadly exists in many agricultural crops, including citrus. However, very limited data are available on Mg-deficiency-responsive microRNAs (miRNAs) in higher plants. Using Illumina sequencing, we isolated 75 (73 known and 2 novel) up- and 71 (64 known and 7 novel) down-regulated miRNAs from Mg-deficient Citrus sinensis leaves. In addition to the remarkable metabolic flexibility as indicated by the great alteration of miRNA expression, the adaptive responses of leaf miRNAs to Mg-deficiency might also involve the following several aspects: (a) up-regulating stress-related genes by down-regulating miR164, miR7812, miR5742, miR3946 and miR5158; (b) enhancing cell transport due to decreased expression of miR3946 and miR5158 and increased expression of miR395, miR1077, miR1160 and miR8019; (c) activating lipid metabolism-related genes by repressing miR158, miR5256 and miR3946; (d) inducing cell wall-related gene expansin 8A by repressing miR779; and (e) down-regulating the expression of genes involved in the maintenance of S, K and Cu by up-regulating miR395 and miR6426. To conclude, we isolated some new known miRNAs (i.e., miR7812, miR8019, miR6218, miR1533, miR6426, miR5256, miR5742, miR5561, miR5158 and miR5818) responsive to nutrient deficiencies and found some candidate miRNAs that might contribute to Mg-deficiency tolerance. Therefore, our results not only provide novel information about the responses of plant to Mg-deficiency, but also are useful for obtaining the key miRNAs for plant Mg-deficiency tolerance.